2020
DOI: 10.21203/rs.3.rs-100668/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alveolar-to-arterial oxygen gradient: role in the management of COVID-19 infection mild population

Abstract: COVID-19 infection is frequently associated with radiological diagnosis of interstitial pneumonia and alteration in gases exchange. We decided to test arterial blood gas assay parameters, in particular alveolar-to-arterial oxygen gradient (AaDO2), in predicting the need of hospitalization, the survival rate and in identifying pneumonia in patients with SARS-CoV-2 infection.We conducted an observational prospective study in one of the Emergency Department of our city. We included consecutive patients with sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, their cutoff value was 56.6 ± 17.5 in the ICU group and 25.9 ± 9.7 in the non-ICU group; given small sample size, strong emphasis cannot be laid upon results. Farina et al 10 also investigated the role of A–a gradient in predicting the need for hospitalization, the survival rate, and identifying pneumonia in patients with SARS-CoV-2 infection. They reported that out of 168 patients with AaDO 2 ≤27, only 3 (1.8%) required readmission within 7 days; it could be attributed to the inclusion of patients with less disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…However, their cutoff value was 56.6 ± 17.5 in the ICU group and 25.9 ± 9.7 in the non-ICU group; given small sample size, strong emphasis cannot be laid upon results. Farina et al 10 also investigated the role of A–a gradient in predicting the need for hospitalization, the survival rate, and identifying pneumonia in patients with SARS-CoV-2 infection. They reported that out of 168 patients with AaDO 2 ≤27, only 3 (1.8%) required readmission within 7 days; it could be attributed to the inclusion of patients with less disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, COVID-19 pneumonia is characterized by both an alveolar and vascular damage [ 3 ]. Even though, few studies have been performed to assess the accuracy of D(A-a)O 2 in early identifying severe COVID-19 pneumonia, and, as far as we know, no previous studies have compared the performance of D(A-a)O 2 and PaO 2 /FiO 2 in this context [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%